RELEVANCE OF ONLINE SOCIAL NETWORKING IN THE TEACHING OF ENGLISH AS A SECOND LANGUAGE IN NIGERIA UNIVERSITIES - Bola Tunde-Awe (European Scientific Journal, ESJ, 2015)
Web-based social networking tools are growing in leaps and bounds and are also popular among adolescent learners. As a result many educators the world over are considering how these tools can be used to enhance online learning and thereby motivate learners to learn and consequently better students’ learning outcomes. This paper investigates the relevance of online social networking media in English as a Second Language in Nigerian Universities. The researcher is the English class teacher, thereby making this study an example of action research. A researcher-designed questionnaire was used to gather data from 200 university undergraduates of Adekunle Ajasin University, Akungba-Akoko, Ondo State, Nigeria. The findings revealed that facebook could serve as an online environment for teaching the two crucial language skills of reading and writing, also be used to enhance confidence in English communication skills. Consequent upon these findings, it is recommended that University undergraduates should use facebook potentials for academic excellence. The implications of the findings were also discussed and recommendations made.